Research on surface roughness of hardox steels parts machined by abrasive waterjet - Filip, Alexandru Catalin (Strojniški vestnik, 2019)
This paper presents an experimental investigation on the abrasive waterjet machining (AWJM) of Hardox steels. A full factorial plan was designed and carried out to determine how the traverse speed, the material thickness, and the material type influence the surface roughness. Two materials were machined during the experiments: Hardox 450 and Hardox 500. The experimental data were analysed using statistical methods, and a mathematical model was obtained. Additional experiments were made to validate the model. The results proved that the analysis is accurate and the mathematical model will be a useful tool in industrial environments for process planning when abrasive waterjet machining is used for the considered material.
Keywords: abrasive waterjet machining; abrazivni vodni curek; Hardox steels; jekla Hardox; obdelava; površinska hrapavost; regresijski model; regression model; surface roughness